Synthesis of rigid poly urehane foams from soybean oil based polyol / Nor Syazana Abu Hanifah - Abu Hanifah, Nor Syazana (2016)
The study is carried out to produced and characterize rigid polyurethane foams from soybean oil. Rigid polyurethane (PU) foams have been prepared from soybean oil- based polyol and was synthesized by using two-steps continuous routes which is epoxy-ring opening followed by alcoholysis process using sulphuric acid as a catalyst. Polyol is identified from hydroxyl functional group using Fourier Transform Infrared Spectroscopy (FTIR) and characterized by acid value. The obtained soybean oil-based polyol was reacted with polymeric diphenylmethane diisocyanate in the presence of water (blowing agent) in a system at NCO/OH ratio of 70/50, 60/50, 50/50 and 40/50 to produce different rigid polyurethane foams. The changes and effects of different NCO/OH ratio on foam properties were studied. Foam rise time and other mechanical properties such as hardness test were evaluated. It was found that the optimum mechanical properties of foams achieved with increasing the NCO/OH ratio. Optical microscopy was used to study the morphology to reveal the cell nature. The cells of all foams showed almost similar closed-cell appearance in microstructure. However, the foams were found to have large cell structure as NCO/OH ratio decreases as it explained a network separation occur during the foam expansion and not homogenously reacted.